Un Caso de Paternalismo Industrial en Tomé: Familia, Espacio Urbano y Sociabilidad de Los Obreros Textiles (1920-1940) - Venegas-Valdebenito, H; Morales-Barrientos, D (Pontificia Universidad Catolica de Chile, 2017)
The aim of this study is to analyze the paternalistic discourse and practice of the Sociedad Nacional de Paños de Tomé, which was located in Concepción. From 1913 to 1940, the Board of Directors of this industry promoted attraction of new textile workers and loyalty among them by family-based recruiting and the selective offering of free housing through which it sought to integrate them into a "community" led by the Welfare Office. This study examines the generous, helpful and inclusive nature of the company s Board of Director s municipal policies. This study is the result of careful analysis of the time s regional press, Coelemu Government Archives and Factory operators notes, completed during the 1930s and 1940s.